SOCIAL DETERMINANTS OF TUBERCULOSIS IN DEVELOPING COUNTRIES - Melkianus Ratu (Jurnal Sahabat Keperawatan, 2022)
Background: The middle - income countries are the highest TB contributors in the world. The trigger for TB is not only identified from the medical aspect but is also related to social determinants of health. Literature review of relevant studies of social determinants of TB can contribute a more comprehensive understanding than that obtained from individual studies alone. It can support the findings and interpretation of one study; describe differences or friction in the findings of the study; facilitate the emerging of new theories; and disseminate the design of new interventions. Methods: The literature search was conducted using the databases of Google Scholar and Scopus. It was performed for a period of one week (12 th–19 th April, 2016). Inclusion criteria were: Articles were published in the period of 2001- 2016, the articles were written in English and studies were conducted in developing countries. Results: Malnutrition, poverty, inadequate housing, educational status, urbanization, and unemployment were the themes emerging from the synthesis process. Conclusions: There were six factors of social determinants of TB that emerged from this literature review. It includes poverty, inadequate housing, malnutrition, educational status, urbanization and unemployment. All the factors are strongly related and tend to have a combined effect as the social determinants of TB